2022
DOI: 10.1073/pnas.2113589119
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin-type and allatostatin-C–type neuropeptides are paralogous and have opposing myoregulatory roles in an echinoderm

Abstract: Somatostatin (SS) and allatostatin-C (ASTC) are inhibitory neuropeptides in chordates and protostomes, respectively, which hitherto were identified as orthologs. However, echinoderms have two SS/ASTC-type neuropeptides (SS1 and SS2), and here, our analysis of sequence data indicates that SS1 is an ortholog of ASTC and SS2 is an ortholog of SS. The occurrence of both SS-type and ASTC-type neuropeptides in echinoderms provides a unique context to compare their physiological roles. Investigation of the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 54 publications
6
23
0
Order By: Relevance
“…This group of 12 C. elegans GPCRs (Data S9) includes NPR-17 that was previously shown to interact with the opioid-like peptide NLP-24 48 . We found two other receptors in this family, NPR-24 and NPR-32, to interact with previously recognized orthologs of the SST/AstC neuropeptide family, NLP-62 and NLP-64 (Figure S2), supporting the conservation of SST/AstC-like receptors in C. elegans 42, 104 .…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…This group of 12 C. elegans GPCRs (Data S9) includes NPR-17 that was previously shown to interact with the opioid-like peptide NLP-24 48 . We found two other receptors in this family, NPR-24 and NPR-32, to interact with previously recognized orthologs of the SST/AstC neuropeptide family, NLP-62 and NLP-64 (Figure S2), supporting the conservation of SST/AstC-like receptors in C. elegans 42, 104 .…”
Section: Resultssupporting
confidence: 78%
“…Indeed, many of the receptors we deorphanized belong to expanded GPCR families for which specific ligands could not have been predicted based on available data, as the corresponding neuropeptide families ( e.g. RFamide, sNPF, and somatostatin-like peptides) have diversified in nematodes as well 42, 104 . The neuropeptide-receptor pairs that we discovered can facilitate future predictions of peptide-GPCR couples in C. elegans as well as other species, such as parasitic nematodes, which may speed up the discovery of drug targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirdly, we have performed a mass spectrometric analysis of radial nerve cord extracts from this species, which has enabled the determination of the mature structure of neuropeptides, as reported previously for many other neuropeptide types [36-40, 42, 43, 45-47] and as reported here for kisspeptin-related neuropeptides. Lastly, we have established A. rubens as an experimental model for functional characterization of neuropeptide signaling systems [36,38,40,41,43,[45][46][47][48][49], which provides a strong basis for future investigations of the physiological roles of kisspeptin-type neuropeptides in this species.…”
Section: Identification and Phylogenetic Analysis Of Echinoderm Kissp...mentioning
confidence: 99%
“…Neuropeptides are considered to be the oldest neuronal signaling molecules in metazoans, which makes them optimal tracers for neuroendocrine activity [ 26 , 27 , 28 ]. Studies of marine invertebrate neuropeptide systems have been revealed in Mollusca, annelids, marine arthropods (crustaceans) and echinoderms [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. In echinoderms, the recent development of RNA high-throughout sequencing technology has allowed strong advances in the identification and characterization of neuropeptides in adults [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%